Automatic main text extraction from web pages - Thi Ha, Phan; Hai Nam, Ha (Vietnam Journal of Science and Technology, 2017)
This paper presents a novel method for extracting body text from web pages used for building text corpus. The algorithm for extracting body text proposed by Aidan Finn [1] is extended with some enhancements in this research. The experimental results on a set of websites show that the proposed method significantly improves the performance of body text extraction without decrease in accuracy compared to the original algorithm.